Ultrasound techniques in the diagnosis of vascular structural changes and blood flow velocity in patients with obstructive sleep apnea - S. E. Bolshakova; I. M. Madaeva; O. N. Berdina; O. V. Bugun; L. V. Rychkova (Кардиоваскулярная терапия и профилактика, 2021)
Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder that increases the risk of cardiovascular disease. Currently, there is a sufficient amount of evidence that OSA increases the risk of cardiovascular diseases, but the mechanisms underlying the formation of these changes remain unclear. The use of Doppler ultrasound and functional stress tests in patients with OSA will make it possible to assess the state of the vascular wall and its changes during treatment. This method can be included in the examination program for patients with sleep-related breathing disorders.